Growth of tomato and cucumber seedlings under different light environments and their development after transplanting - Liu, Xiaojuan; Shi, Rui; Gao, Meifang; He, Rui; Li, Yamin; Liu, Houcheng (Frontiers in Plant Science, 2023)
Selecting suitable light conditions according to the plant growth characteristics is one of the important approaches to cultivating high-quality vegetable seedlings. To determine the more favorable LED light conditions for producing high-quality tomato and cucumber seedlings in plant factories with artificial light (PFALS), the growth characteristics of tomato and cucumber seedlings under seven LED light environments (CK, B, UV-A, FR, B+UV-A, UV-A+FR, and B+FR) and the development of these seedlings after transplanting into a plastic greenhouse were investigated. The results showed that the seedling height and hypocotyl length increased in treatments with far-red light supplementation (FR, UV-A+FR, and B+FR), but decreased in the B treatment, in both varieties. The seedling index of tomato seedlings increased in the B+UV-A treatment, while that of cucumber seedlings increased in the FR treatment. After transplanting into a plastic greenhouse, tomato plants that radiated with UV-A had greater flower numbers on the 15th day after transplanting. In cucumber plants of the FR treatment, the flowering time was significantly delayed, and the female flower exhibited at a lower node position. By using a comprehensive scoring analysis of all detected indicators, light environments with UV-A and FR were more beneficial for improving the overall quality of tomato and cucumber seedlings, respectively.